Planning elective surgeries Analysis and comparison in a real case - Marques, Inês (2009)
This work focus on hospital surgical suite optimization, mainly in the efficient use of the operating rooms when planning elective surgeries. We studied a real case in a hospital in Lisbon. An integer linear programming model was developed to weekly schedule elective surgeries for the hospital surgical suite. The model was tested with real data collected from the hospital records. Non-optimal solutions obtained were improved with a simple and efficient improving heuristic. All solutions have actually improved through this process. These results were finally analyzed and compared with the ones the hospital really performed. The analysis shows that the solutions obtained by our approach improve the use of the surgical suite while respecting the conditions imposed by the hospital. The analysis also shows that the plans obtained by the proposed approach can be implemented.